Pemberdayaan Ekonomi Lokal melalui Penguatan Strategi Pemasaran UMKM Keripik Singkong “Nek Surati” di Kampung Dolok Kecamatan Bosar Maligas Kabupaten Simalungun - Syahrul Tanjung; Mursal Amri Harahap; M Taufiq Aldiansyah; Heri Yunus; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving local economic development, particularly in rural areas that rely on the utilization of local natural resources. However, many MSMEs still face challenges in marketing aspects, especially limited use of digital technology, weak branding, and unattractive product packaging. This community service activity aims to strengthen the marketing strategy of the “Nek Surati” cassava chips MSME located in Dolok Village, Nagori Boluk, Bosar Maligas District, Simalungun Regency. The methods employed include field observations, interviews with MSME actors, descriptive analysis of existing problems, and practice-based (hands-on) assistance through digital marketing training, improvement of packaging design, and strengthening of product branding. The results indicate an increase in the digital readiness of the MSME actor, as evidenced by the adoption of WhatsApp Business, the creation of digital product catalogs, and the utilization of social media as a promotional tool. In addition, improvements in packaging design and brand identity enhanced the visual appeal and product image in the eyes of consumers. This assistance activity had a positive impact on improving the marketing capacity of the MSME and opened opportunities for expanding market reach. With continuous assistance, the “Nek Surati” cassava chips MSME has the potential to increase its competitiveness and contribute more significantly to the local economy.